AI-Driven Service Transformation : Revolutionizing Operational Excellence - Ashok Sreerangapuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Service industries are undergoing rapid transformation through the integration of artificial intelligence (AI) and automation. This article presents an AI-powered service delivery model that autonomously optimizes operations, improves customer satisfaction, and drives business growth. The article leverages AI algorithms to automate incident management, predict operational disruptions, and enhance customer experiences. Real-world implementations within retail, healthcare, and technology sectors demonstrate significant improvements in service efficiency, with operational costs reduced by 30% and customer satisfaction scores increasing by 30%. This article proposes AI-driven service enhancements as a game-changer in the delivery of complex, scalable, and reliable services.